Agreement between photographic screening and hospital biomicroscopy grading of diabetic retinopathy and maculopathy. - Healy, R; Sallam, A; Jones, V; Donachie, P; Scanlon, P; Stratton, I; Johnston, R (Wichtig Editore s.r.l., 2014)
PURPOSE: To examine the level of agreement and reasons for disagreement between grading of diabetic retinopathy and maculopathy using mydriatic digital photographs in a diabetic retinopathy screening service (DRSS) and hospital eye service (HES). METHODS: English NHS Diabetic Eye Screening Programme grades for diabetic retinopathy prospectively recorded on a hospital electronic medical record were compared to the grades from the DRSS event that prompted referral. In cases of disagreement, images were reviewed. RESULTS: Data for 1,501 patients (3,002 eyes) referred between 2008 and 2011 were analyzed. The HES retinopathy grades were R0 (no retinopathy) in 341 eyes, R1 (background retinopathy) in 1,712 eyes, R2 (pre-proliferative retinopathy) in 821 eyes, and R3 (proliferative retinopathy) in 128 eyes. The DRSS grades were in agreement in 2,309 eyes (76.9%), recorded a lower grade in 227 eyes, and recorded a higher grade in 466 eyes. Agreement was substantial (κ = 0.65). The commonest cause for disagreement was overgrading of R1 as R2 by hospital clinicians. The HES maculopathy grades were M0 (no maculopathy) in 2,267 eyes and M1 (maculopathy) in 735 eyes. The DRSS were in agreement in 2,111 eyes (70.2%), recorded a lower grade in 106 eyes, and recorded a higher grade in 785 eyes. Agreement was fair (κ = 0.39). The commonest cause for disagreement was hospital clinicians missing fine exudates. CONCLUSIONS: This study establishes a benchmark standard for agreement between HES and DRSS grading. Review of DRSS and grading reports images for newly referred patients is likely to improve levels of agreement, particularly for diabetic retinopathy, and should be strongly encouraged.